1997
DOI: 10.1046/j.1471-4159.1997.69041767.x
|View full text |Cite
|
Sign up to set email alerts
|

Site Mutation in the Rat μ‐Opioid Receptor Demonstrates the Involvement of Calcium/Calmodulin‐Dependent Protein Kinase II in Agonist‐Mediated Desensitization

Abstract: The rat 1z-opioid receptor (rMOR1), expressed in human embryonic kidney 293 (HEK293) cells, showsa desensitization to the inhibitory effect of the js agonist DAMGO on adenylate cyclase activity within 4 h of DAMGO preincubation. To investigate the role of calcium/calmodulin-dependent protein kinase Il (CaM kinase Il) on 1s-opioid receptor desensitization, we coexpressed rMOR1 and constitutively active CaM kinase Il in HEK293 cells. This coexpression led to a faster time course of agonist-induced desensitizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…Down-regulation of hMOR S268P was otherwise unaltered, suggesting that the absence of this putative phosphorylation site has no obvious consequences on long term agonist-induced regulation. We cannot exclude, however, that there may be an impairment of rapid agonist-induced desensitization, as was shown for the S261A/S266A mutant in the rat (56) or recently suggested for the human S268P mutant (57).…”
Section: N40d N152d R265h and S268p Polymorphism In The -Opioid Rementioning
confidence: 71%
See 2 more Smart Citations
“…Down-regulation of hMOR S268P was otherwise unaltered, suggesting that the absence of this putative phosphorylation site has no obvious consequences on long term agonist-induced regulation. We cannot exclude, however, that there may be an impairment of rapid agonist-induced desensitization, as was shown for the S261A/S266A mutant in the rat (56) or recently suggested for the human S268P mutant (57).…”
Section: N40d N152d R265h and S268p Polymorphism In The -Opioid Rementioning
confidence: 71%
“…Site-directed mutagenesis of this serine residue into alanine was described previously in the rat -opioid receptor (56). The authors found no impairment of agonistinduced inhibition of adenylyl cyclase when a double mutant receptor (S261A/S266A) was expressed in HEK cells, as well as no impairment of agonist-evoked increase in inward K ϩ currents using the Xenopus oocyte expression system.…”
Section: N40d N152d R265h and S268p Polymorphism In The -Opioid Rementioning
confidence: 89%
See 1 more Smart Citation
“…Whether phosphorylation of Ser 363 and Thr 358 involved a GRK remains to be demonstrated. Some reports suggested that agonist-induced phosphorylation of the opioid receptors could be mediated by Ca 2+ /calmodulin-dependent protein kinase II (26), or by mitogen-activated protein kinase (27), but the amino acid motif surrounding Thr 358 or Ser 363 does not correspond to that of either kinase. Thus, it is tempting to suggest that a yet unknown Ser/Thr kinase is responsible for the DPDPEinduced phosphorylation of DOR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phosphorylation by G protein receptor kinases following agonist treatment has been proposed to play a role in opioid receptor desensitization and tolerance (2). Other serine/ threonine kinases such as protein kinase C and calcium/calmodulin-dependent kinase II in some systems may also regulate opioid receptors (3).…”
mentioning
confidence: 99%